2002
DOI: 10.1067/mva.2002.118823
|View full text |Cite
|
Sign up to set email alerts
|

Significance of endoleaks after endovascular repair of abdominal aortic aneurysms: The EUROSTAR experience

Abstract: phology. One of the remaining concerns is uncertainty about the long-term effect of persistent blood flow within the aneurysm sac after endovascular grafting, an occurrence known as endoleak. 1 In fact, endoleak development constitutes one of the prime reasons to perform postoperative surveillance by regularly performed image studies, usually computed tomography (CT) scanning. [2][3][4] The main purpose of EAR is to prevent death from rupture of the aneurysm, and early identification of endoleaks is intended t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
302
1
11

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 450 publications
(325 citation statements)
references
References 45 publications
11
302
1
11
Order By: Relevance
“…In agreement with other authors, our management strategy for type II endoleak is conservative, and repair is indicated in case of hemodynamic importance with high flow and an increase in aneurysm size [27][28] . There were 14 (8.8 %) secondary type II endoleaks observed in our (Fig.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In agreement with other authors, our management strategy for type II endoleak is conservative, and repair is indicated in case of hemodynamic importance with high flow and an increase in aneurysm size [27][28] . There were 14 (8.8 %) secondary type II endoleaks observed in our (Fig.…”
Section: Discussionsupporting
confidence: 49%
“…Our experience with EVAR complications requiring intervention is comparable with other presented reports. Type I endoleaks, especially the late proximal ones, are absolutely indicated for repair, and this was also the case in our patients [27][28] . In our early experience, immediate type Ia endoleaks in our patients were caused by failed stentgraft placement in the short conical neck.…”
Section: Discussionmentioning
confidence: 93%
“…Onda emitida por el microhilo al variar la tensión producida sobre un molde de silicona La amplia variabilidad de la presión del saco aneurismático tras la exclusión endovascular de un aneurisma de aorta es uno de los problemas a los que se enfrenta la cirugía endovascular actualmente. Se ha demostrado que la presencia de fugas durante el seguimiento es un factor pronóstico de complicaciones durante el seguimiento de estos pacientes (129) . Las pruebas diagnósticas disponibles en la actualidad no siempre son capaces de diagnosticar dichas fugas existiendo casos en la literatura de rupturas del saco aneurismático en ausencia de fugas (130) .…”
Section: Aplicaciones Del Mh En El Futurounclassified
“…[1] Type 1 endoleaks are associated with an increased risk of post-procedural aneurysm rupture and late aneurysm related death, and re-intervention is recommended as soon as possible upon the diagnosis. [1] Anatomical segments of the aneurysm neck can create a predisposition for type 1 endoleaks.…”
mentioning
confidence: 99%
“…[1] Type 1 endoleaks are associated with an increased risk of post-procedural aneurysm rupture and late aneurysm related death, and re-intervention is recommended as soon as possible upon the diagnosis. [1] Anatomical segments of the aneurysm neck can create a predisposition for type 1 endoleaks. [1] Several factors such as short neck, a neck degree higher than 60, thrombus or plaque in the neck wall, mural calcifications, ulcers in the neck may increase the type 1 endoleaks after the stent-graft placement.…”
mentioning
confidence: 99%